Perancangan Ruang Pamer dan Produk Furnitur dengan Pendekatan Desain Multifungsi oleh Hanani Studio - Witjahjo, Franzeska Stephani; Nuradhi, Maureen (KREASI, 2024)
The population of Indonesia from year to year is predicted to continue to increase, and the social conditions that are influencing and currently taking place are that most people will look for comfort and beauty in choosing the furniture they will use. The lifestyle of most people in the city is also changing due to increasingly significant cultural and social shifts. For example, many people are switching to apartments or houses with limited land due to expensive land prices. Hanani Studio is a business that manufactures furniture and provides related services. As a furniture business that applies the principles of compact space furniture with a multifunctional design, it is hoped that it can be a solution for people with limited residential land so that it can answer their needs. A key component of this design is the use of geometric shapes and the emphasis on the material. Shapes are taken from basic geometric shapes by reducing or separating the basic shapes and using good-quality materials at affordable prices. Utilizing woven rattan, a feature of the Indonesian native way of life, as the primary focal point in shops for home decor and furniture. The furniture that is currently in the Hanani Studio showroom is a product of ready-to-use furniture and custom furniture. This design emphasizes that a multifunctional design approach in designing showrooms and furniture products not only provides practical solutions to space limitations but also offers added value in terms of aesthetics and innovation, improving the overall quality of life of users.